Evaluating the Influence of Smart City Frameworks on Urban Mobility: A Comparative Perspective with Manaus, Brazil - Andrade, Ricardo; Oliveira, Marcelo Augusto Macedo Junior (Journal of Progress in Civil Engineering, 2026)
This study examines the application and challenges associated with the implementation of the Urban Mobility Law (Law No. 12,587/2012) in the city of Manaus, with a focus on the difficulties in providing public transport services and the regulatory shortcomings that perpetuate issues such as overcrowding and low-quality service. The research contextualizes Manaus within a scenario of increasing mobility demand, shaped by distinct geographic and socioeconomic characteristics that necessitate tailored strategies for developing a more efficient and inclusive transport system. Smart cities—which leverage technology to enhance transportation—serve as a benchmark for urban mobility solutions that prioritize user well-being. With an emphasis on regulatory oversight and the impact of concession contracts, the study investigates the roles of the municipal government and private concessionaires, drawing comparisons with successful practices implemented in other Brazilian cities. Methodologically, the research adopts an exploratory and comparative approach, based on document and legislative analysis, to propose viable solutions aimed at fostering more equitable and accessible urban mobility in Manaus.